Grammar Plays an Important Role in Teaching Foreign Languages (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article highlights the importance of grammar for language learners; moreover, it is the basis of any language. By grasping the grammatical structure of a foreign language, learners can decode and understand written and spoken texts more efficiently. A solid foundation in grammar allows learners to identify verb tenses, sentence structure, and word order, leading to improved comprehension skills.